Frequency of Impacted Third Molar in Mandibular Angle Fractures in Patients Presenting to Ayub Teaching Hospital - Jawad Ahmad, Alaf Khan, Muhammad Jamal, Anam Javed, Jawad Ahmad, Alaf Khan, Muhammad Jamal, Anam Javed (Journal of Rawalpindi Medical College, 2022)
Mandibular fractures are one of the commonest maxillofacial injury. Fractures take place at various locations. Mandibular angle fracture susceptibility in addition to being associated to the type and direction of impact is also associated with impacted 3rd molar.The objective of the study is to determine the frequency of impacted third molar in mandibular angle fracture.This descriptive cross-sectional study was performed for a period of six months on one hundred and twenty-two patients with mandibular. OPG was done to determine the state of 3rd molar tooth. The states of 3rd molar tooth along with its inclination were noted on a proforma.The frequency of 3rd molar impaction in fractures of angle of mandible was 36.1%. Young age (less than 31 years in this study) was significantly associated with development of impacted 3rd molar tooth (p < 0.05).Individuals with impacted 3rd molar should be educated about the possibility of the fracture of mandibular angle so that preventive measures can be adopted.